Affirming versus Relating: Steps around, toward, and away from Dance and Performance Art. Issue 3 (2nd September 2017) - Brandão, Mariana
ABSTRACT: This essay establishes distinctions between dance, an art of affirmation and convergence, and performance art, an art of relation and divergence. While dance generates new dimensions of time and space, performance art reconfigures the various elements it employs. Thus, in dance, interpretation always corresponds to an authorial role, evident in the dancer's quality of presence, unique to each performance. This problem engaged modernists, who advocated the use of the machine or puppet in place of flesh-and-blood performers, distancing dance from the concerns of Futurists and performance artists.